The sleepers in the cave: quran stories for little hearts - Khan, Saniyasnain (GoodwordKidz New Delhi, 2004)
This narrative recounts the story of a group of young believers who seek refuge in a cave and are miraculously preserved through sleep for many years. It symbolizes faith, divine protection, and the endurance of belief across time.